The effect of mixed salts in gel-coated polymer electrolyte for advanced lithium battery - Kum, KS; Song, MK; Kim, YT; Kim, HS; Cho, BW; Rhee, HW (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
A miscible blend solution of poly(ethylene glycol diacrylate) (PEGDA)/poly(vinylidene fluoride) (PVdF)/poly(methyl methacrylate) (PMMA) was crosslinked on polypropylene (PP) separator by UV-irradiation. PEGDA/PVdF/PMMA(EN/M)-coated electrolytes showed much better liquid electrolyte uptaking and retention than PEGDA/PP composite electrolyte because viscous ternary blend solution was more compatible with electrolyte system. Gel-coated membranes (GCE) containing a mixed lithium salts of LiPF6/LiCF3SO3 (10/1 (w/w)) showed slightly lower maximum conductivity than those containing only LiPF6, but their interfacial resistance much more stable than other salt compositions. In addition, it was found that gamma-Al2O3 filler improved interfacial stability. As a result, 8 cm x 13 cm MCMB/LiCoO2 cells composed of E/V/M-coated composite matrix and LiPF6/LiCF3SO3 (10/1 (w/w)) delivered 99.6% initial capacity after 100 cycles at C/2 rate. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: MEMBRANES